Learning model Cooperative Audio Visual Assisted Mind Mapping on Social Sciences Learning Outcomes in Class VI at SDN 16 Bungku - Wahyudin S. Amin; Juraid; Nuraedah (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Basic Education is level basic education​ education intermediate . As for goals education at school base is For obtain education from the teacher who gave it lesson , improve potency Study as well as know to what extent discipline Study participant learn at school . Formulation problem implementation of learning models cooperative Mind Mapping assisted by visual videos implement learning in class VI SDN 16 Bungku , results Study student using a learning model cooperative assisted by visual videos. Research purposes For know How implementation of learning models cooperative Mind Mapping assisted by visual videos implement learning in class VI SDN 16 Bungku . For know results Study student using a learning model cooperative assisted by visual videos. Study This is study descriptive qualitative with method data collection used are : observation , study documents , and interviews . Research result Presentation of data at SDN 16 Bungku Regency Morowali , obtained through method observation , interviews , and documentation . In research on this , the presentation of the data is based focus study namely : first : Implementation of the Learning Model Cooperative Mind Mapping Assisted by In-Depth Visual Video Implement it Learning in Class VI SDN 16 Bungku , second : results Study student using a learning model cooperative assisted by visual videos.